THE EFFECT OF ADDITION OF ESSENTIAL OIL FROM CEREH LEAVES TO PERTALITE FUEL ON EMISSIONS OF WASTE GAS - Imam Prasetyo Imam; M. Arieq Nasabi (Scientific Journal of Mechanical Engineering Kinematika, 2020)
Essential oils are volatile compounds at room temperature derived from aromatic plants (such as vetiver, cloves, lemongrass, nutmeg, cananga, cinnamon) because the content of these essential oils has many benefits, including improving engine performance, cleaning fuel injectors, reduce the deposition of organic compounds in the combustion chamber, and can save fuel consumption and reduce exhaust emissions. The purpose of this study was to determine how much influence the addition of essential oil to pertalite fuel to reduce the concentration of CO and HC and increase CO2 levels in motorized vehicles. This test was carried out by adding the percentage of essential oil mixing as much as 6 ml, 12 ml, and 18 ml on pertalite fuel with engine speed variations of 1000, 1500, 2000, 2500, and 3000 rpm. Based on the test results, it was found that several significant decreases in the emission concentration value of CO levels occurred at the engine speed of 2000 rpm - 3000 rpm. The percentage of essential oil 12 ml is down by 0.30% from 1.02% to 0.72% at 3000 rpm engine speed. While the concentration of emission levels of HC from engine speed of 1500 rpm - 3000 rpm has decreased significantly, at 3000 rpm engine speed for 12 ml of essential oil percentage decreased by 30 ppm from 185 ppm to 155 ppm.